1996
DOI: 10.1143/jjap.35.6463
|View full text |Cite
|
Sign up to set email alerts
|

Precise Stress Control of Ta Absorber using Low Stress Alumina Etching Mask for X-Ray Mask Fabrication

Abstract: In the stress control of an X-ray mask absorber, the repeatability of control and stability are important. We found that the change in the stress in a Ta film resulting from annealing depends on the oxygen concentration in the film; the magnitude of the stress change is determined by the annealing temperature and time. Using this characteristic of Ta film, we have successfully controlled the stress in the Ta absorber to less than 5 MPa with good repeatability. In our mask fabrication proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…According to a report, the stress-change in air is much larger than that in nitrogen, 13) which has been explained by oxygen diffusion into Ta film. [13][14][15] The stresschange is increased with annealing temperature and time, and is directly proportional to the diffused oxygen content in Ta film. 13) Additionally, the large distance of oxygen diffusion into Ta film is understood to be due to the high diffusion rate of oxygen along the grain boundaries of the Ta.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a report, the stress-change in air is much larger than that in nitrogen, 13) which has been explained by oxygen diffusion into Ta film. [13][14][15] The stresschange is increased with annealing temperature and time, and is directly proportional to the diffused oxygen content in Ta film. 13) Additionally, the large distance of oxygen diffusion into Ta film is understood to be due to the high diffusion rate of oxygen along the grain boundaries of the Ta.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15] The stresschange is increased with annealing temperature and time, and is directly proportional to the diffused oxygen content in Ta film. 13) Additionally, the large distance of oxygen diffusion into Ta film is understood to be due to the high diffusion rate of oxygen along the grain boundaries of the Ta. 13,15,16) In this paper, we investigated the effect of oxygen diffusion on the stress-hysteresis behavior of Ge 2 Sb 2 Te 5 , as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…XRD analysis was not performed on Ta 5 B. Previous work 4,5,13 has shown that ␤-Ta films deposited at low pressures had a fibrous, dense structure, while films deposited at higher pressures were less dense with an open columnar structure. Oxygen diffusion along grain boundaries and eventually into the grains, resulted in an observed change of stress in the compressive direction.…”
Section: B Materials Characterizationmentioning
confidence: 99%
“…X-ray lithography using synchrotron radiation (SR) is a promising technology for fabricating ultra large scale integration (ULSI) devices with dimensions less than 0.1 p.m, because it has a superior characteristics such as high resolution and throughput [1][2][3][4][5]. Since the current x-ray lithography is a proximity printing system, x-ray mask is the most critical element in this technology.…”
Section: 1ntroductonmentioning
confidence: 99%